1997
DOI: 10.1038/386671a0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of angiogenesis

Abstract: After the developing embryo has formed a primary vascular plexus by a process termed vasculogenesis, further blood vessels are generated by both sprouting and non-sprouting angiogenesis, which are progressively pruned and remodelled into a functional adult circulatory system. Recent results, particularly from the study of mice lacking some of the signalling systems involved, have greatly improved our understanding of the molecular basis underlying these events, and may suggest new approaches for treating condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
3,443
3
130

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 5,157 publications
(3,651 citation statements)
references
References 47 publications
24
3,443
3
130
Order By: Relevance
“…In this study, we demonstrated the superior angiogenic capacity of aFGF in the HUVEC tube formation assay. This was described before for endothelial cell assays 46. To our opinion it is remarkable that in many studies VEGF is used as angiogenic therapeutic.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, we demonstrated the superior angiogenic capacity of aFGF in the HUVEC tube formation assay. This was described before for endothelial cell assays 46. To our opinion it is remarkable that in many studies VEGF is used as angiogenic therapeutic.…”
Section: Discussionmentioning
confidence: 92%
“…In response to angiogenic stimuli, endothelial cells degrade the basement membrane by secreting proteolytic enzymes that include metalloproteinases (MMPs) and serine proteases [1,2,37]. The cells then migrate through the degraded basement membrane and continue to break down the interstitial stroma as they move.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to proteolytic enzyme secretion and migration, tube morphogenesis depends on endothelial cell proliferation [1,2,37,38]. Analysis of cell growth and cell cycle profile upon TO-IFI16 infection suggests that sustained expression of IFI16 affects HUVEC proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasculogenesis is the formation of discrete blood vessels in situ from endothelial cell precursors, and angiogenesis is the formation of blood vessels by sprouting and extending from pre-existing vessels (reviewed in Risau, 1997;Hanahan, 1997). Vasculogenesis is responsible for the larger vascular network, including the dorsal aorta and the yolk sac, while angiogenesis is required for the vascularization of organs such as the brain and kidney, as well as the remodeling of capillary networks.…”
Section: Introductionmentioning
confidence: 99%